Dehydroevodiamine and hortiamine, alkaloids from the traditional Chinese herbal drug Evodia rutaecarpa, are IKr blockers with proarrhythmic effects in vitro and in vivo. (May 2018) - Baburin, Igor; Varkevisser, Rosanne; Schramm, Anja; Saxena, Priyanka; Beyl, Stanislav; Szkokan, Phillip; Linder, Tobias; Stary-Weinzinger, Anna; van der Heyden, Marcel A.G.; Houtman, Marien; Takanari, Hiroki; Jonsson, Malin; et al.
Graphical abstract: Abstract: Evodiae fructus is a widely used herbal drug in traditional Chinese medicine. Evodia extract was found to inhibit hERG channels. The aim of the current study was to identify hERG inhibitors in Evodia extract and to investigate their potential proarrhythmic effects. Dehydroevodiamine (DHE) and hortiamine were identified as IKr (rapid delayed rectifier current) inhibitors in Evodia extract by HPLC-microfractionation and subsequent patch clamp studies on human embryonic kidney cells. DHE and hortiamine inhibited IKr with IC50 s of 253.2 ± 26.3 nM and 144.8 ± 35.1 nM, respectively. In dog ventricular cardiomyocytes, DHE dose-dependently prolonged the action potential duration (APD). Early afterdepolarizations (EADs) were seen in 14, 67, 100, and 67% of cells after 0.01, 0.1, 1 and 10 μM DHE, respectively. The proarrhythmic potential of DHE was evaluated in 8 anesthetized rabbits and in 8 chronic atrioventricular block (cAVB) dogs. In rabbits, DHE increased the QT interval significantly by 12 ± 10% (0.05 mg/kg/5 min) and 60 ± 26% (0.5 mg/kg/5 min), and induced Torsade de Pointes arrhythmias (TdP, 0.5 mg/kg/5 min) in 2 rabbits. In cAVB dogs, 0.33 mg/kg/5 min DHE increased QT duration by 48 ± 10% ( P <  0.05*) and induced TdP in 2/4 dogs. A higher dose did not induce TdP. In human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs), methanolic extracts of Evodia, DHE and hortiamine dose-dependently prolonged APD. At 3 μM DHE and hortiamine induced EADs. hERG inhibition at submicromolar concentrations, APD prolongation and EADs in hiPSC-CMs and dose-dependent proarrhythmic effects of DHE at micromolar plasma concentrations in cAVB dogs should increase awareness regarding proarrhythmic effects of widely used Evodia extracts.